Two-step hepatic artery reconstruction for a hepatic artery lacking in length for the use of a microclamp in living donor liver transplantation - Okochi, Masayuki (Int J Surg Case Rep, 2016)
INTRODUCTION: We describe successful two-step hepatic artery reconstruction in a patient whose graft site hepatic artery was too short for the use of a microclamp in living donor liver transplantation. PRESENTATION OF CASE: A 57-year-old woman was diagnosed as having hepatitis C and liver cirrhosis. Her 26-year-old son was the living liver donor. The living donor underwent right lobectomy. The dissected graft hepatic artery was too short for the use of a microclamp. The recipient right hepatic artery was cut and used as an arterial graft. The graft right hepatic artery was sutured to the right hepatic artery of the arterial graft and the graft posterior branch of the right hepatic artery was sutured to the middle hepatic artery of the arterial graft. After reconstruction of the portal vein and hepatic vein was completed, anastomosis was performed between the graft right hepatic artery and right hepatic artery. The patency of the vessels was checked using color Doppler ultrasonography for 1 week postoperatively. No postoperative complications involving blood flow of the hepatic artery were observed. DISCUSSION: In our case, the recipient hepatic artery was cut and used as an arterial graft. Although the number of anastomotic sites of the hepatic artery increased, we could perform hepatic artery reconstruction safely and easily. CONCLUSION: Two-step hepatic artery reconstruction is a useful method in cases where the recipient hepatic artery does not have enough length.